Towards Ontology-Driven Verification of Car Claims Settlement - Pancerz, Krzysztof; Wolski, Jacek (Wydawnictwo Politechniki Łódzkiej, 2023)
In the paper, we outline an intelligent tool enabling the users to automatize the process of verification of the car claims settlement. Two data sources power the tool. The first one is the source of car images in which damaged elements are recognized. The second one is the source of PDF files in which cost estimates are extracted. The designed ontology of car repair, described in the paper, is used both in the pre-processing step and in recognition of a typical situations.
Keywords: OWL; ontology of car repairing; deep learning; image recognition; claims settlement; OWL; ontologia naprawy samochodów; głębokie uczenie się; rozpoznawanie obrazu; likwidacja szkód